L. Seed Oil Modulates Dyslipidemia and Neuronal Dysfunction in Tramadol-Induced Toxicity in Wistar Albino Rats - Ezebuilo Ugbala Ekpono; Patrick Maduabuchi Aja; Udu Ama Ibiam; Peter Chinedu Agu; Ejike Daniel Eze; Adam Moyosore Afodun; Osita Gabriel Okoye; Josiah Eseoghene Ifie; Ayomide Victor Atoki (SAGE Publishing, 2024)
Objective: The modulating effects of Cucurbita pepo seed oil (CPSO) on dyslipidemia and neuronal dysfunction in tramadol toxicity were studied. Methods: Fifty-six albino rats were divided into seven groups of eight rats each after a 2-week acclimatization period. All animals had unrestricted access to water and feed, and treatments were administered orally once daily for 42 days. Glutamate dehydrogenase and glutaminase activities were assessed using brain homogenate, while lipid profiles were analyzed in serum samples. Results: Tramadol toxicity was evidenced by significant ( P < 0.05) increases in brain glutamate dehydrogenase along with significant ( P < 0.05) decreases in the activities of glutaminase in the group administered only tramadol. Also, serum levels of total cholesterol, LDL-C and triglycerides also increased significantly ( P < 0.05) following administration of tramadol with decreased level of HDL-C ( P < 0.05). However, treatment with CPSO significantly restored the activities and levels of the altered biochemical parameters in a dose-dependent manner. The results of the biochemical investigation using the lipid profile and the enzymes of glutamate metabolism were corroborated by the results obtained from the histopathological examination of the brain. Conclusion: The results of this study therefore suggest that tramadol-induced dyslipidemia and neuronal dysfunction be managed and prevented by the administration of Cucurbita pepo seed oil.